Blue ocean tourism in Asia and the Pacific: Trends and directions before the coronavirus crisis - John Connell (Asian Development Bank Institute (ADBI), 2020)
Tourism has played only a marginal part in the blue economy of the region of Asia and the Pacific. Most Asian and the Pacific islands and island states have sought some form of tourism development. Promoting tourism and finding markets has usually come from hotels, travel agents, and national and regional tourism bodies, all of which can be remote from local people. Remote areas and islands are disadvantaged. Resorts can alienate land, and occasionally marine, resources and contribute to a coastal squeeze. Tourism generates employment, but not always for local people, and spawns a considerable informal sector. Linkages with agriculture are hard to generate on islands; hence much food is imported. Tourism projects may be sensitive to environmental management. Diverse outcomes reflect the nature of the islands (as independent states or peripheral places); their social and economic status; the scale and structure of development (from backpackers and national parks to resorts and cruises); the willingness of tourists, tourism entrepreneurs, and government agencies to engage with local people; previous experience; and the ability of tourism to meet the need for sustainable development. COVID-19 brought an abrupt end to buoyant cruise ship tourism, and the closure of national borders led to the demise of island tourism. Typically, in Vanuatu and Samoa, resorts, restaurants, and other components of the formal and informal sectors closed down. Much employment was lost (especially of women), creating development problems at every level, alongside a reversion to self-reliance, raising questions over the future of tourism industries and national and island economies.
Keywords: Z32; 330; tourism; Pacific islands; blue economy; employment; incomes; environment; coronavirus